2016
DOI: 10.1371/journal.pone.0149521
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Six Strategies to Treat Recurrent Clostridium difficile Infection

Abstract: ObjectiveTo assess the cost-effectiveness of six treatment strategies for patients diagnosed with recurrent Clostridium difficile infection (CDI) in Canada: 1. oral metronidazole; 2. oral vancomycin; 3.oral fidaxomicin; 4. fecal transplantation by enema; 5. fecal transplantation by nasogastric tube; and 6. fecal transplantation by colonoscopy.PerspectivePublic insurer for all hospital and physician services.SettingOntario, Canada.MethodsA decision analytic model was used to model costs and lifetime health effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 51 publications
2
79
0
2
Order By: Relevance
“…Similar results have been demonstrated by other economic analyses evaluating FMT for treatment of recurrent CDI [10,14,15]. A cost-effectiveness analysis of strategies for treatment of recurrent CDI performed from a societal perspective in the USA concluded that FMT via colonoscopy was cost-effective with an ICER of $17,016 compared with vancomycin at a willingness-to-pay threshold of $50,000/QALY [10].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar results have been demonstrated by other economic analyses evaluating FMT for treatment of recurrent CDI [10,14,15]. A cost-effectiveness analysis of strategies for treatment of recurrent CDI performed from a societal perspective in the USA concluded that FMT via colonoscopy was cost-effective with an ICER of $17,016 compared with vancomycin at a willingness-to-pay threshold of $50,000/QALY [10].…”
Section: Discussionsupporting
confidence: 76%
“…A recent study performed in Canada compared 6 strategies to treat recurrent CDI using the perspective of the Ontario Ministry of Health and Long-Term Care. The authors concluded that FMT via colonoscopy dominated all other strategies in the base case at a willingness-to-pay threshold of $50,000/QALY [15]. However, route of FMT often depends on the delivery method which is considered the safest for the patient [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrent CDI is a prime example of this phenomenon. While metronidazole has the lowest list price of all registered CDI treatments, it is the least cost-effective option, due to its high associated recurrence rate [11].…”
mentioning
confidence: 99%